(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article gives importance to the ecalogic state of the gods with a high risk of technogen, the study of their negative impact on the lands, and the tasks on which the work carried out on them was put forward.